Meningkatkan Berpikir Kritis dan Hasil Belajar PAK Dengan Model Problem Based Learning (PBL) Pada Materi Suara Hati Kelas X SMA N 1 Air Putih - Juniati Naibaho (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The research background is the lack of critical thinking skills and student learning outcomes, apart from that the learning method used is not appropriate, namely using lectures without variation while the characteristics of the material are understanding and analysis. This research aims to find out how to apply the Problem Based Learning model and whether Problem Based Learning can improve critical thinking skills and student learning outcomes in teaching materials on conscience, critical thinking and responsibility for the influence of mass media by applying the Pancasila profile of critical thinking dimensions. The subjects of this research were students in class X-3 of SMA N 1 Air Putih with a total of 9 students consisting of 2 men and 7 women. This research is classroom action research carried out in 2 cycles. This type of research uses observation, interviews and study test results. The data analysis technique used qualitatively consists of data reduction in the form of descriptions, graphs, tables and drawing conclusions that refer to the problem formulation. The results of the research show that teacher activity in applying the Problem Based Learning model in the learning process increases at each meeting, as well as student activity increases at each meeting. The application of the Problem Based Learning model can increase students' critical thinking skills from 77.77% in cycle 1 to 96% in cycle 2. Likewise, the application of the Problem Based Learning model can increase student learning outcomes, namely 62.09% in cycle 1, increasing to 93.52% in cycle 2. So, using the Problem Based Learning model according to the syntax can improve critical thinking skills and student learning outcomes.